The Begoniaceae of Colombia The Begoniaceae of Colombia - Smith Lyman B.; Schubert Bernice G. (Caldasia)
Begonia (§ Poecilia) semiovata / Begonia (? § Poecilia) subcostata / Begonia (§ Poecilia) filipes / Begonia (§ Poecilia) hirtella / Begonia (§ Begoniastrum) microcarpa / Begonia (? § Hydristyles) ophiogyna / Begonia (§ Huszia.) pastoensis / Begonia (§ Saueria) sulcata / Begonia (§ Regoniastrum) tovarensis / Begonia (? §) magdalenae / Begonia (? §) cryptocarpa / Begonia (§ Begoniastrum) fagopyroides / Begonia (§ Scheidweileria) parviflora / Begonia (§ Gobenia) Maurandiae / Begonia (§ Gobenia) tropaeolifolia / Begonia (§ Gobenia) spadiciflora / Begonia (§ Hydristyles) novo-granatae / Begonia (§ Begoniastrum) cucullata / Begonia (? §) tiliaefolia / Begonia (§ Pilderia) buddleiaefolia / Begonia (§ Ruizopavonia) Rossmanniae / Begonia (? § Ruizopavonia) extensa / Begonia (§ Ruizopavonia) Cuatrecasana / Begonia (§ Ruizopavonia) xylopoda / Begonia (§ Ruizopavonia) cymbalifera. Begonia (§ Poecilia) semiovata / Begonia (? § Poecilia) subcostata / Begonia (§ Poecilia) filipes / Begonia (§ Poecilia) hirtella / Begonia (§ Begoniastrum) microcarpa / Begonia (? § Hydristyles) ophiogyna / Begonia (§ Huszia.) pastoensis / Begonia (§ Saueria) sulcata / Begonia (§ Regoniastrum) tovarensis / Begonia (? §) magdalenae / Begonia (? §) cryptocarpa / Begonia (§ Begoniastrum) fagopyroides / Begonia (§ Scheidweileria) parviflora / Begonia (§ Gobenia) Maurandiae / Begonia (§ Gobenia) tropaeolifolia / Begonia (§ Gobenia) spadiciflora / Begonia (§ Hydristyles) novo-granatae / Begonia (§ Begoniastrum) cucullata / Begonia (? §) tiliaefolia / Begonia (§ Pilderia) buddleiaefolia / Begonia (§ Ruizopavonia) Rossmanniae / Begonia (? § Ruizopavonia) extensa / Begonia (§ Ruizopavonia) Cuatrecasana / Begonia (§ Ruizopavonia) xylopoda / Begonia (§ Ruizopavonia) cymbalifera.